PENGARUH PEMBERIAN PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomea reptans Poir) - Syafri Edi (Bioplantae, 2014)
The increasing demand for vegetables should be offset by the increasing of production. Kangkung is one of short-lived plants and the price can be reached by various circles of society. Therefore, kangkung can be used as food diversification in Indonesia. To get good quality vegetables and optimal yield, fertilization is a very important technology. Fertilization aims to add nutrients to the plants so that the plants can grow and produce well. The study aims to determine the effect of using organic fertilizer on the growth and yield of kangkung in yards. The study was conducted at Andil Jaya Village, Jelutung District, Jambi City, from March to June 2013. Kangkung planted in polybags size 40x50 cm, using topsoil and organic fertilizers. Research using randomized block design, test the combination treatment of organic fertilizer and soil, namely: (a) 100% soil (control), (B) 75% soil plus 25% organic fertilizer, (C) 50% soil plus 50% organic fertilizer, and (D) 25% soil plus 75% organic fertilizer. Each treatment was repeated 8 (eight) times. The results showed that organic fertilizer plays a role in the growth and yield of kangkung, treatment B and C can provide kangkung with maximum growth and yield. Keywords : kangkung, organic fertilizer, yards